Increasing incidence of HIV‐ associated tuberculosis in Romanian injecting drug users. Issue 5 (21st February 2018) - Oprea, C; Ianache, I; Calistru, PI; Nica, M; Ruta, S; Smith, C; Lipman, M
Abstract : Background: A high prevalence of tuberculosis (TB) among HIV‐positive injecting drug users (IDUs) may fuel the TB epidemic in the general population of Romania. We determined the frequency and characteristics of TB in HIV‐infected IDUs referred to a national centre. Methods: Prospective observational cohort study of all newly‐diagnosed HIV‐positive IDUs admitted to Victor Babes Hospital, Bucharest, between January 2009 and December 2014. Socio‐demographics, clinical characteristics and outcomes of HIV/TB co‐infected IDUs were compared to HIV‐positive IDUs without TB. Results: 170/598 (28.5%) HIV‐infected IDUs were diagnosed with TB. The prevalence increased from 12.5% in 2009 to 32.1% in 2014 ( P < 0.001). HIV/TB co‐infected individuals had lower median CD4 cell counts 75 ( vs . 450/mm 3, P < 0.0001) and higher median HIV viral loads 5.6 log10 ( vs . 4.9 log10, P < 0.0001) when presenting to healthcare services. 103/170 (60.6%) HIV/TB co‐infected IDUs were diagnosed with pulmonary TB. Resistant Mycobacterium tuberculosis strains were common, with 18/105 (17.1%) of patients having Multi‐Drug Resistant (MDR) disease. Higher mortality rate was associated with TB co‐infection ( P < 0.0001), extra‐pulmonary TB ( P = 0.0026) and extensively drug resistant TB ( P = 0.024). Conclusions: Tuberculosis (TB) is an increasing problem in HIV‐infected IDUs in Romania. Presentation is often with advanced HIV, significant TB drug resistance and consequent outcomes are poor.